Benzoquinone-assisted heterogeneous activation of PMS on Fe3S4 via formation of active complexes to mediate electron transfer towards enhanced bisphenol A degradation. (1st November 2022) - Liu, Xiwen; Shao, Penghui; Gao, Shanshan; Bai, Zhaoyu; Tian, Jiayu
Highlights: Benzoquinone (BQ) promoted the heterogeneous process of PMS activation by Fe3 S4 . Degradation and mineralization of bisphenol A (BPA) were enhanced when BQ was injected into Fe3 S4 /PMS system. PMS and BQ were activated to active complexes (BQ-PMS*) on the surface of Fe3 S4 . BPA would be directly oxidized by BQ-PMS*. Abstract: Benzoquinone (BQ) is of great significance for enhancement of contaminants degradation in the homogeneous oxidation system of peroxymonosulfate (PMS). However, the role of BQ in the heterogeneous activation of PMS for contaminants oxidation is still not clear. Herein, this work reported that the addition of BQ into the Fe3 S4 /PMS system could effectively enhance the degradation and mineralization of bisphenol A (BPA). Mechanistic study uncovered that the BQ and PMS would form active complexes (BQ-PMS*) on the surface of Fe3 S4 and the excited BQ-PMS* can oxidize the BPA. To be specific, the electron of BPA was extracted by BQ-PMS* and then transfer to the surface of Fe3 S4 . The surface electron can induce the change of valence state of S and Fe elements, which can trigger the degradation of BPA and inhibit the decomposition of BQ itself. To the best of our knowledge, it is the first time to unveil the positive role of BQ in the heterogeneous activation of PMS, which may shed new light on the establishment of high-efficient PMS-based oxidation technology for remediation of organic pollutant. Graphical abstract: Image, graphical abstract